Profile of Self-Regulated Learning on First-Year Students at Science Education Department in Online Learning - Evelina Astra Patriot; Pandu Jati Laksono (Universitas Sebelas Maret, 2024)
Online learning requires students to study independently and manage lectures according to the time set. Researchers need to know the criteria for self-regulated learning of first-year students at the Physics Education Department. This paper aims to determine self-regulated learning during online learning. The study used a quantitative research approach with a survey method. The Online Self-Regulated Learning Questionnaire (OLSQ) collected the data, a 20-item scale with a 5-point Likert-type response format. The sample of this study was 131 students of physics and chemistry education study programs. Each was randomly selected to see how their respective study programs implemented independent learning activities during online learning. The results showed that each indicator of independent learning in online learning received a positive response through the OLSQ instrument that had been distributed. The disciplined behavior indicator has a higher percentage, followed by the exercise self-control indicator. Generally, the pre-service students have self-regulated learning with high criteria. This result can provide a good contribution and open for further research. The implication of this research can be a reference for lecturers to improve online and self-regulated learning quality.